2005
DOI: 10.1016/j.intcom.2005.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Affordance as context

Abstract: The concept of affordance is relatively easy to define, but has proved to be remarkably difficult to engineer. This paradox has sparked numerous debates as to its true nature. The discussion presented here begins with a review of the use of the term from which emerges evidence for a two-fold classification-simple affordance and complex affordance. Simple affordance corresponds to Gibson's original formulation, while complex affordances embody such things as history and practice. In trying to account for comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 14 publications
1
76
0
3
Order By: Relevance
“…This gave in-depth understanding into the influence of simulation media on ergonomics identification and evaluation of these eight events. This in-depth understanding is obtained within the boundaries of the two case studies, which in some degree limits the generalizability (Thomas, 2011). However, findings of common patterns between cases are argued to be strengthened when the cases vary in maximum degree (Flyvbjerg, 2006;Neergaard, 2010).…”
Section: Methodological Limitations Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…This gave in-depth understanding into the influence of simulation media on ergonomics identification and evaluation of these eight events. This in-depth understanding is obtained within the boundaries of the two case studies, which in some degree limits the generalizability (Thomas, 2011). However, findings of common patterns between cases are argued to be strengthened when the cases vary in maximum degree (Flyvbjerg, 2006;Neergaard, 2010).…”
Section: Methodological Limitations Of the Studymentioning
confidence: 99%
“…These naturally occurring simulation activities provided a unique opportunity for studying, how the fidelity and affordance of these two types of simulation media may influence the ability to identify and evaluate ergonomics conditions. We approached the simulation activities of the two hospital design projects as two case studies, each constituting of four simulation events viewed as nested units of analysis (Thomas, 2011). The simulation activities in both cases had the purpose of providing input to the engineers and architects, who designed the new hospital buildings during complex design processes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their experimental study Oshlyansky et al (2004) showed clear cultural differences in how basic physical affordances (like a light switch) are perceived differently in different countries, leading to a breakdown of the affordance. This relationship between affordances and the context in which they are perceived are underlined by the theoretical examination of Turner (2005), who states that Bfrom a holistic or phenomenological perspective, affordance, use and context are one^. A concrete, yet conceptual, example of social affordances is the 10 'Motivation Affordances' by Zhang (2008), that describe how learning can be facilitated through a number of social, psychological and emotional affordances.…”
Section: Social Affordancesmentioning
confidence: 99%
“…These extensions of the classic affordance concept (Norman 1988) into social affordances (Bradner et al 1999;Kreijns and Kirschner 2001;Turner 2005) indicate a need to provide more precise distinctions between physical or perceived affordances, and the social effect of those affordances. Although reconceptualizations of the affordance concept into broader Technology Affordances, that enable mediated actions (Kaptelinin and Nardi 2012), provides new insights and analytical possibilities, we subscribe to the proposition of McGrenere and Ho (2000) that we can solidify and extend the existing affordances concept.…”
Section: Collaborative Affordancesmentioning
confidence: 99%